Antimicrobial and Antioxidant Effects of Some Turkish Fodder Plants Belongs to Fabaceae Family (Vicia villosa, Trifolium ochroleucum and Onobrychis altissima) - Erbil, Nurcan; Duzguner, Vesile; Durmuskahya, Cenk; Alan, Yusuf (Oriental Scientific Publ Co, 2015)
In this study, the antimicrobial and antioxidant activities of Vicia villosa, Trifolium ochroleucum and Onobrychis altissima samples were investigated. For this purpose, plant extracts were tested against 3 fungus, 4 Gr(-) and 3 Gr(+) bacteria; additionally the glutathione (GSH) level and total phenolic content were measered spectrophtometrically and total antioxidant capacity (TAC) was done by ELISA method. According to results methanolic extracts of Vicia villosa, Trifolium ochroleucum and Onobrychis altissima exhibited no antimicrobial activities against test microorganisms. Trifolium ochroleucum extract has the highest levels for GSH and TAC (462.06 +/- 25.89 mmol/L, 30.35 +/- 0.003 mg GAE/g dw respectively). Vicia villosa extract is showed the highest antioxidant capacity (4.416 +/- 0.107 mM).